Outcomes of Direct Lumbar Spondylolysis Reconstruction by Bone Graft and Fixation Using Pedicular Screw Rod Laminar Hook Construct - Khaled Omran, MD. (Egyptian Spine Association, 2019)
Background Data: Lumbar spondylolysis is often managed by conservative methods in most patients. Operative interference is indicated in symptomatic patients not responding to medical treatment or patients with multilevel pars defect. Purpose: To evaluate the clinical, functional, and radiological results of bone graft and pedicular screw fixation and rod laminar hook construct in treatment of lumbar spondylolysis. Study Design: A prospective clinical case cohort study. Patients and Methods: Between October 2017 and January 2019, fifteen patients with symptomatic lumbar spondylolysis not responding to conservative treatment for more than 6 months were treated by reconstruction of pars defect by bone block autografting and fixation using pedicular screw laminar hook construct. The mean follow-up was 9.47±3.07 months. All patients were examined pre- and postoperatively and they were followed up clinically; for measuring their pain scale, Visual Analogue Scale (VAS); functionally, Oswestry Disability Index (ODI); radiologically (pars defect healing). Perioperative outcomes and complications were documented. Results: Clinical, radiological, and functional outcomes were significantly improved. Bony union was evident in all patients (100%). Blood loss, operative time, and hospital stay were reported. Two cases reported complications in this study: misplaced pedicular screw and superficial wound infection. Conclusion: Direct reconstruction of pars defect by bone graft and fixation using pedicular screw rod laminar hook construct is an effective feasible procedure in treating lumbar spondylosis. It preserves lumbar motion and hence may decrease adjacent segment problems. (2019ESJ194)